2021
DOI: 10.1038/s41598-021-97025-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of charge accumulation of poly(heptazine imide) gel

Abstract: Photo-stimuli response in materials is a fascinating feature with many potential applications. A photoresponsive gel of poly(heptazine imide), PHI, termed PHIG, exhibits photochromism, photoconductivity, and photo-induced charge accumulation, and is generated using ionic liquids and PHI. Although there are several examples of ionic liquid gels that exhibit photochromism and photoconductivity, this is the first report of an ionic liquid gel that exhibits both these properties as well as charge accumulation. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
21
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 29 publications
5
21
1
Order By: Relevance
“…The wavelength of maximum absorbance in the absorption band on the long-wavelength side that appears by light irradiation is approximately 640 nm for both K-PHI:PMMA and K-PHI:IL. The change in the absorption band of K-PHI due to photochromism was also consistent with that of the K-PHI solution. ,,, The previous study has reported that isolated crystallites of K-PHI tend to aggregate upon freeze-drying. The optical gap of such solid K-PHI was found to increase substantially over the original K-PHI due to a decrease in the conjugation length of the PHI framework and partial detachment .…”
supporting
confidence: 80%
See 4 more Smart Citations
“…The wavelength of maximum absorbance in the absorption band on the long-wavelength side that appears by light irradiation is approximately 640 nm for both K-PHI:PMMA and K-PHI:IL. The change in the absorption band of K-PHI due to photochromism was also consistent with that of the K-PHI solution. ,,, The previous study has reported that isolated crystallites of K-PHI tend to aggregate upon freeze-drying. The optical gap of such solid K-PHI was found to increase substantially over the original K-PHI due to a decrease in the conjugation length of the PHI framework and partial detachment .…”
supporting
confidence: 80%
“…K + would undergo repeated collisions with ions in EmimPF 6 and polymer chains in PMMA. In fact, our previous report showed that the more viscous the ionic liquid is, the slower the rate of color recovery after the K-PHI composite was discolored by photochromism . This suggests a decrease in the mobility of K + in the composite owing to its interaction with the ionic liquid.…”
mentioning
confidence: 96%
See 3 more Smart Citations